Raritná komplikácia po staplerovej hemoroidektómii - Šuchá, R; Duchoň, R; Pinďák, D; Dolník, J (Rozhledy v chirurgii, 2013)
Statistics show that more than half of the population suffers from hemorrhoids at different clinical stages. Only a small percentage of them (5 to 10%) require surgical treatment. The gold standard is open hemorrhoidectomy (most commonly Milligan-Morgan operation). Circular stapled hemorrhoidopexy by Longo is an alternative to conventional hemorrhoidectomy. The main advantages of this procedure are: less postoperative pain, earlier return to work and to social life. The complication rate is similar to open hemorrhoidectomy. This method, however, also brings new kinds of complications, some of them potentially life-threatening. Our case report presents one of these rare complications.
Keywords: Hemorrhoidectomy; pooperační bolest; Pain, Postoperative; mužské pohlaví; lidé; hemoroidy; Male; hemoroidektomie; Surgical Stapling; chirurgická technika pomocí přístrojů a svorek; Humans; Hemorrhoids